Marion takes charge - Barkley, Callie (Barkley, Callie. Critter Club, 2015)
When Marion finally gets the chance to babysit her little sister, she finds that the task is harder than she expected, especially when she gets called to the Critter Club to help with a stray cat and must bring Gabby along.